2012
DOI: 10.1007/s00128-012-0671-2
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Dynamics of the Insecticide: Clothianidin (Dantop 50 % WDG) in a Tea Field Ecosystem

Abstract: The fate of clothianidin [(E)-1-(2-chloro-1, 3-thiazol-5-ylmethyl)-3-methyl-2-nitroguanidine] applied to tea plant was studied at two location in West Bengal, India. The insecticide was applied in Tea field at two doses @30 and 60 g.a.i./ha during June-July 2009. Solid-phase extraction and liquid-liquid extraction was employed for the determination of this insecticide in tea samples. Clothianidin residues were analyzed and estimated quantitatively by HPLC at λ(max) 250 nm. The observed half life values of made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Thiamethoxam was expected to cause the least mortality via both foliar application methods (100 to 17% at 0 and 60 m downwind). A more realistic estimate of mortality could take into account the insecticide half‐lives (chlorpyrifos, 4–6 d [Galietta et al 2011; Szpyrka et al 2017]; chlorantraniliprole, 3–17 d [Lee et al 2019; Szpyrka et al 2017]; imidacloprid, 2–5 d [Mukherjee and Gopal 2000; Banerjee et al 2012]; thiamethoxam, 4–6 d [Rahman et al 2015]; and clothianidin, 4 d [Chowdhury et al 2012]), which are shorter than the length of the entire larval stage (12–13 d at 27 and 25 °C, respectively [Rawlins and Lederhouse 1981; Zalucki 1982]). Assuming an insecticide half‐life of 4 d, estimated exposure would drop approximately 2.4‐fold for neonates that hatch on the day of application and 4.8‐fold for neonates that hatch 4 d later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiamethoxam was expected to cause the least mortality via both foliar application methods (100 to 17% at 0 and 60 m downwind). A more realistic estimate of mortality could take into account the insecticide half‐lives (chlorpyrifos, 4–6 d [Galietta et al 2011; Szpyrka et al 2017]; chlorantraniliprole, 3–17 d [Lee et al 2019; Szpyrka et al 2017]; imidacloprid, 2–5 d [Mukherjee and Gopal 2000; Banerjee et al 2012]; thiamethoxam, 4–6 d [Rahman et al 2015]; and clothianidin, 4 d [Chowdhury et al 2012]), which are shorter than the length of the entire larval stage (12–13 d at 27 and 25 °C, respectively [Rawlins and Lederhouse 1981; Zalucki 1982]). Assuming an insecticide half‐life of 4 d, estimated exposure would drop approximately 2.4‐fold for neonates that hatch on the day of application and 4.8‐fold for neonates that hatch 4 d later.…”
Section: Discussionmentioning
confidence: 99%
“…Krishnan et al (2020) estimated field-scale acute topical and dietary risks to different larval instars following single foliar applications of beta-cyfluthrin, chlorantraniliprole, chlorpyrifos, imidacloprid, and thiamethoxam (acute foliar risks for clothianidin presented in Supplemental Data, Table S1). The half-lives of these insecticides on growing plants range from 1 to 17 d (Mukherjee et al 2000;Galietta et al 2011;Banerjee et al 2012;Chowdhury et al 2012;Szpyrka et al 2017;Lee et al 2019). Consequently, larvae that survive the initial exposure from a spray drift event, as well as larvae that hatch from eggs laid after a spray drift event, could be exposed to insecticide residues through a significant portion of their life stage, which ranges from 12 to 13 d (Rawlins and Lederhouse 1981;Zalucki 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the pseudostems and bulbs were more like a transport channel, with little wileyonlinelibrary.com/journal/ps storage of pesticides. In previous studies, the dissipation of clothianidin in tea, 25 tomato, 26 crown daisy, sedum and amaranth were determined, 27 and its half-lives were different: 4.07-4.63 days in green tea, 15.6 days in green tomato and 16.8 days in ripe tomato. Li et al 26 also found that different applied dosages could affect the dissipation of clothianidin, with high concentrations persisting.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the analytical method for determining the clothianidin residues in brown rice, hull, straw, paddy water and paddy sediment samples was derived from the reference methods using the QuEChERS clean-up technique (Lehotay et al 2005; Chowdhury et al 2012; Wang et al 2012).…”
Section: Methodsmentioning
confidence: 99%